Enhanced BoxMuller method for high quality Gaussian random number generation. (2018) - Addaim, Adnane; Gretete, Driss; Madi, Abdessalam Ait
Fast and highquality Gaussian random number generation (GRNG) is a key capability for simulations across a wide range of disciplines. In this article, we present an enhanced BoxMuller method for GRNG using one uniform variable. Its probability density function (PDF) is given in closed form as a function of one parameter. In this article, the theoretical basis of this method is quite thoroughly discussed and is evaluated using several different statistical tests, including the chisquare test and the AndersonDarling test. The simulations results show good performances of this method which generates accurately a true Gaussian PDF even at very high σ (standard deviations) values in comparison with the standard BoxMuller method.